PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Agustianingrum, Shintia Selvi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research intend to analyze and test the influence of profitability, liquidity, capital structure, company growth, and company size on company value. Population includes automotive and component sub-sector companies listed on the IDX period 2018-2022. The sample selection technique used was purposive sampling, so 35 observation data were obtained. The research method used multiple linear regression with SPSS 25. Research results claimed that profitability had a positive influence on company value. Liquidity and company size had a negative influence on company value, meanwhile capital structure and company growth had no influence on company value. Profitability, liquidity, capital structure, company growth, and company size simultaneously affect company value.